THE ROLE OF COMMUNICATION IN THE BUYING AND NEGOTIATION PROCESS - Lani, Oktri Permata (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
Individuals and individuals who are members of an organization cannot achieve their goals and cannot even carry out their lives if they do not cooperate with other parties. Today, competition among companies in Indonesia is growing, especially in the sale of cars and spare parts. These symptoms can be seen from the price competition for cars and spare parts which vary greatly from one company to another, namely from low prices with standard quality to high prices with good quality. This is what makes a company compete to improve the quality of basic car materials and spare parts at prices that are affordable by the community. Negotiation is a process of interaction in an offer made by two or more parties, who want to achieve their respective interests and realize that in order to achieve all of their interests, they must relate to each other and direct each other's interests in order to achieve the benefit of all parties. In this case, the agreement between the two parties on the price quote is carried out by the customer and the company's negotiator. Based on the background of the problem described above, the authors formulate the main problem as follows: